REVITALISASI PENDIDIKAN YANG BERBASIS NASIONALISME : POSISI KHAS SEJARAH MEMBANGSA INDONESIA - Anhar Gonggong (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2008)
This paper studies the importance of revitalizing the nationalism based education in Indonesia. The study starts with finding the relationship between education and nationalism during the Dutch occupation. It is then followed by the relevance between education and nationalism as the root of the Indonesian national movement. The writer gives examples of education which is developed by Muhammadiyah and Taman Siswa as an effort of revitalizing nationalism based education. At the end of this paper there will discussion on the importance of history subject in building the spirit of nationalism and patriotism. Key words: educational revitalization, nationalism, Indonesia